Seventh-Day Adventist Views and Stances on Same-Sex Marriage: Consideration for Its Pastors - Pardosi, Milton Thorman (8ISC Proceedings: Theology, 2022)
Marriage is an institution that God established in the garden of Eden on the sixth day of Creation week. Marriage has entered a troubling era of change with the rise of divorces and same-sex marriages. There are religious and political groups that reject it, but some accept it. This is also an issue in both Christianity and the Seventh-day Adventist Church. That is why it is necessary to review the Bible’s principles of marriage so that Christians understand the correct principles of marriage in the Bible. Marriage in the Bible is between one man and one woman according to their nature. Marriage and same-sex intercourse are abominations before God. The researcher found out that there are two models of same-sex marriage emerging at this time. First, same-sex marriage between man and man or woman and woman by nature. Second, same-sex marriage between man and “woman” as a result of genital surgery or woman with “man” as a result of genital surgery. The second type can bring confusion to the church. The researcher suggested that the church and pastors need to take steps medically to ensure that the prospective partners are naturally different, not the result of genital surgery. The Seventh-day Adventist Church rejects same-sex marriage in both the first and second models. Keywords: Marriage, Same-Sex, Nature